1997
DOI: 10.1046/j.1464-410x.1997.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose versus multiple instillations of epirubicin as prophylaxis for recurrence after transurethral resection of pTa and pT1 transitional‐cell bladder tumours: a prospective, randomized controlled study

Abstract: Objective To compare single-dose and multiple instilthe patients treated with epirubicin than in the control group (24, 25 and 52%, respectively; P<0.001). In lations of epirubicin in the chemoprophylaxis of superficial bladder tumours.those receiving epirubicin, the rates of recurrence were statistically comparable (P=0.9). Patients who had a Patients and methods In a prospective randomized and controlled study, 168 evaluable patients were large tumour burden showed slightly lower recurrence rates with single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 2 publications
0
40
0
Order By: Relevance
“…No differences were found in trials comparing one immediate instillation to either 8 weekly instillations starting 1-2 wk after TUR followed by monthly instillations to 1 yr (18 instillations) [16] or to weekly instillations for 6-8 wk followed by monthly instillations to 1 yr (16-18 instillations) [17]. In another trial comparing one immediate instillation to 4 weekly instillations starting 2 wk after TUR followed by monthly instillations to 1 yr (15 instillations), fewer patients had recurrences in the delayed multiple instillation group, 24.8% versus 30.2% (p = 0.05) [12].…”
Section: In Low-risk Patients Can the Same Or Better Results Be Obtamentioning
confidence: 93%
“…No differences were found in trials comparing one immediate instillation to either 8 weekly instillations starting 1-2 wk after TUR followed by monthly instillations to 1 yr (18 instillations) [16] or to weekly instillations for 6-8 wk followed by monthly instillations to 1 yr (16-18 instillations) [17]. In another trial comparing one immediate instillation to 4 weekly instillations starting 2 wk after TUR followed by monthly instillations to 1 yr (15 instillations), fewer patients had recurrences in the delayed multiple instillation group, 24.8% versus 30.2% (p = 0.05) [12].…”
Section: In Low-risk Patients Can the Same Or Better Results Be Obtamentioning
confidence: 93%
“…Significant local toxicities often prevent patients to fulfill all schedules. Recently, some studies have revealed that a single instillation immediately after TUR-Bt prevents recurrences (7,(18)(19)(20)(21). Oostelinck et al (18) first demonstrated that a single instillation clearly prevented recurrence for patients with a single tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic effect of single 80 mg of epirubicin equals that of consecutive 40 mg of epirubicin or mitomycin C (18,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Two large-scale randomized control trials confirmed that an immediate intravesical administration of epirubicin could decrease the recurrence rate [2,3] . However, some patients gained little clinical benefit from the intravesical therapy because of poor sensitivity of cancer cells to these chemicals.…”
mentioning
confidence: 93%